Survey on function of political parties in regulating the relations of the triple branches ,comparative study in the systems of England, America and Iran - Faeghe Chalabi; Rajab Izadi; kamaladin Herisinejad (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2019)
Political parties in democratic systems are considered as intermediate institutions of democratic regimes by organizing political power, mobilizing popular forces and regulating the relating power. Political parties plays an important role in regulating the reciprocal relations of the ruling powers; the influence of parties in the interactions of the legislative and executive power has created a dramatic changes in the division of the classical powers of contemporary states. On the other hand, political circles sometimes talk about changing the political system of Iran to the parliamentary system or the legislature’s transforming into two parliamentary chambers; on the other hand, the interrelationships between the legislative and executive bodies are faced with deadlocks. One of the requirements for solving such challenges is the existence of parties in the political system; Therefore, this article examines the function of parties in regulating the relations of powers in the United Kingdom, United States and Iran as a  parliamentary, presidential and semi-presidential systems, seeks to identify the disadvantages and advantages of party systems in countries such as the United Kingdom and the United States as party success styles and to explain the challenges of interfering in the interactions of the Iranian state by eliminating the existing shortcomings.